The Impact of Globalization on Regional Economic Transformation in Indonesia - Annisa Fitri; Febia Roylani; Silvi Sudarsih; Yulia Novita; Hasbi Dwi Rofita (Council: Education Journal of Social Studies, 2025)
Globalization provides opportunities for local products to enter the global market. However, it has an impact on the increasing competition between domestic and foreign companies in the global market, and the increasing economic disparity between regions and between community groups. The purpose of writing this article is to describe in general the impact of globalization on regional economic transformation in Indonesia. The method used is a literature review of several published articles and a theoretical approach using the triangulation method to find the ideal answer to the topic raised. The search results indicate that regional economic changes in Indonesia, triggered by globalization, are evident in the shift in economic structure, the movement of labor from traditional to modern sectors, and changes in production methods that have become more efficient and intensive. The Indonesian government is addressing this dynamic with policies that support investment, enhance workforce skills, and diversify the economy to reduce dependence on specific sectors. Implementing the right strategy and cooperation between the government, private sector, and society, globalization can be utilized to encourage inclusive and sustainable economic growth. However, it is also very important to preserve local wisdom so that Indonesia's cultural identity is not lost.